Uji Aktivitas Fraksi N-Heksana Ekstrak Metanol Bangle (Zingiber cassumunar Roxb.) sebagai Terapi Komplementer Malaria secara In Vivo (The Activity Test of N-Hexane Fraction of Bangle (Zingiber cassumunar Roxb.) Methanolic Extract as Complementary Thera - Sarah Andriani; Bagus Hermansyah; Sugiyanta Sugiyanta (Pustaka Kesehatan, 2017)
Malaria is one of endemic disease in Indonesia that caused many deaths. Immune system plays important rules in preventing malaria severity. Bangle has been proven as an immunostimulant and could reduce parasitaemia in malaria infection. This study aimed to determine the activity of n-hexane fraction of bangle methanolic extract as complementary therapy of malaria. This study used 28 mice, divided into one positive control group, one negative control group, and five treatment groups. Bangle stimulation before induction was given to five treatment groups with dose: 0,005625mg/grbw, 0,01125mg/grbw, 0,0225mg/grbw, 0,045mg/grbw, and 0,09mg/grbw for 14 days. Plasmodium berghei induction was given to all groups, and then treatment groups were given ACT and bangle fraction, and positive control group was given ACT without fraction for three days. Parasitaemia was observed everyday, then plasmodium growth inhibition percentation was counted. Bangle fraction stimulation gave lower parasitaemia at the begining and Pearson correlation test showed strong positive correlation between dose of bangle fraction and plasmodium growth inhibition percentation (p<0,01). We can conclude that n-hexane fraction of bangle methanolic extract was active as complementary therapy of malaria (IC50=0,013 mg/grbb). Keywords: malaria, bangle, n-hexane, complementary therapy